P-132 Malignant Potential of Colonic Tumor-Associated Fibroblasts in a Model of Inflammation-Induced Carcinogenesis. (March 2016) - Patel, Deep; Kalter, Valerie; Questore, Olivia; Desai, Sagar; Rutch, Logan; Gutierrez, Linda
Abstract : Background: The crosstalk between epithelial cells and the stromal components of the intestine is quite important to maintain its homeostasis. Stromal cells play a critical role in the development of inflammatory bowel disease and colorectal cancer as well. Thrombospondin 1 (TSP-1) is an anti-angiogenic protein that mainly interacts with a variety of cells and growth factors in the stroma. In this study, colonic inflammation-induced cancers were developed and tumor associated fibroblasts (TAF) lacking TSP-1 were isolated. These fibroblasts were characterized in vitro and its tumorigenic properties tested in vivo by using a syngeneic implantation model. Methods: Wild type (WT) and TSP-1 deficient (TSP-1 −/− ) mice were injected with a single dose of azoxymethane (AOM), while 2% dextran sodium sulfate was administered during multiple cycles. Tumors were dissected and TAF were isolated and cultured. Proliferation assays were carried out, as well as the wound-healing assay, which was used to test the migratory properties of these cells. WT (n = 18) and TSP-1 −/− (n = 13) mice were subcutaneously injected with 1 × 10 6 WT and TSP-1 deficient fibroblasts into the flanks. Tumor growth was monitored for 5 weeks before tumors were harvested, fixed, embedded in paraffin, cut and stained for histological evaluation. Immunohistochemistry for leucine-rich repeat-containing G-protein coupled receptor 5 (LgR5) was performed as well, since these fibroblasts expressed LgR5 in the original colonic cancers. Results: In vitro studies showed no major differences in proliferation and cell migration between WT and TSP-1 deficient TAF. However, TSP-1 deficient colonic fibroblasts were able to generate fibrosarcomas with moderate invasiveness in 100% of the mice injected reaching diameters up to 28 mm. Conversely, WT fibroblasts were unable to develop as tumors after multiple attempts. Immunohistochemical evaluation of LgR5 in these fibrosarcomas showed focal positive staining in the periphery but expression of LgR5 was negative in most of these malignant fibroblasts. Conclusions: Colonic TAF with a deficiency in TSP-1 has high tumorigenic potential. This malignant phenotype is developed only upon contact with the stromal environment in vivo, resulting in moderate invasive fibrosarcomas. These results underline the importance of matricellular proteins such as TSP-1, which may regulate the mesenchymal epithelial interactions in the colonic environment.